Running themselves into the ground? Incidence, prevalence, and impact of injury and illness in runners preparing for a half or full marathon - Franke, T. P. C.; Backx, M. J. B.; Huisstede, B. M. (Journal of Orthopaedic & Sports Physical Therapy, 2019)
Objective: To describe the incidence, prevalence, and impact of running-related injuries (RRIs) and illness symptoms in half marathon and marathon runners during the 16-week period before the Utrecht Marathon. Methods: In this prospective cohort study, we used the Oslo Sports Trauma Research Center questionnaire to register RRIs and illness symptoms every 2 weeks during the 16-week study period. When an injury or illness occurred, questions were added regarding its nature. We calculated the incidence proportion (the number of new cases divided by the number of runners at risk) and the period prevalence (the number of existing and new cases within a 2-week period, divided by the total number of runners at risk during that period). Results: Of the 161 included runners, 9 out of 10 reported an RRI or illness symptom at some time during the study period. In any 2-week period, 5.6% to 14.8% of the runners reported a new RRI, and 6.3% to 13.8% of the runners reported a new illness symptom. The prevalence of RRIs ranged from 29.2% to 43.5%, and the prevalence of illness symptoms ranged from 28.3% to 71.2%. The most prevalent RRIs were in the lower leg (prevalence range, 5.4%-12.3%) and knee (prevalence range, 2.7%-9.3%). The most prevalent illness symptoms were rhinorrhea/sneezing (prevalence range, 3.9%-12.7%) and coughing (prevalence range, 3.9%-11.9%). The incidence and prevalence of illness symptoms peaked at the same time as the influenza-like illness epidemic of the winter of 2015-2016. Conclusion: Nine out of every 10 runners reported an RRI or illness symptom in the lead-up to a half or full marathon. In any 2-week period, up to 1 in 7 runners reported a new RRI or illness symptom.